Tinjauan Yuridis Terhadap Putusan Nomor:0548/Pdt.G/2016/Pa.Gtlo Di Pengadilan Agama Gorontalo - Siti Nur Setia Rahman; Muh. Amin Dali; Suslianto Suslianto (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The problems raised in this research are (1) whether the inheritance distribution according to decision number: 0548/Pdt.G/2016/PA.Gtlo has been realized on yulianti boki while the barrier is still alive? (2) how do judges mediate the inheritance case number: 0548/Pdt.G/2016/PA.Gtlo in the Gorontalo religious court? This research aimed to determine the realization of the decision number: 0548/Pdt.G/2016/PA.Gtlo on the distribution of inheritance to Yuliyanti Boki, the heir of the Mahjub. To analyze how judges mediate inheritance disputes through decision number: 0548/Pdt.G/2016/PA.Gtlo at the Gorontalo Religious Court, this type of research is field research, namely field observations of the object being studied in order to obtain data that is relevant to matters relating to the problems studied and which focuses on the results of data collection from informants who have been determined, namely the judges of the Gorontalo Religious Court. The judge’s decision showed that Yuliyanti Pakaya was not the primary heir but the mahjub heir who was not entitled to receive the inheritance. However, Yuliyanti Pakaya was still given the distribution of inheritance by the primary heirs voluntarily through the results of mediation conducted by the Gorontalo Religious Court judges.